Not so ‘arm's length’: reinterpreting agencies in UK central government - Elston, T (Wiley, 2014)
Administrative decentralization to government agencies (so‐called ‘agencification’) has attracted much attention in recent years, increasingly for its longevity or evolution after the ‘high’ managerialism of the 1980s, and largely through a neo‐positivist epistemology. Drawing on techniques of narrative and discourse analysis, and a model of incremental ideational change, this article identifies the necessity of supplementing those existing large‐N analyses of agencification's expansion and decline with qualitative attention to the endurance of policy meaning. It demonstrates how the original foundations of managerialism, civil service empowerment and decentralization from the UK's seminal ‘Next Steps’ agency programme are eschewed in contemporary reform discourse, where agencification is instead advocated as centralized, politically proximate and departmentalized governance. This substantial reinterpretation of the arm's‐length concept not only challenges existing claims of continuity in UK administrative policy, but also demonstrates the utility of interpretive methods for exploring longevity in public management more widely.